Analisis Kualitatif Budaya Organisasi dan Implikasinya terhadap Kinerja Pendidik dalam Perspektif Psikologi Organisasi Positif - Irfieh, Fauzia; Madaniah, Lilim Halimatul; Sanusi, Hary Priatna (Melati Institute, 2026)
Efforts to improve educator performance often rely on structural approaches and material incentives, while the dimensions of meaning, values, and subjective experience within the school's organizational culture receive insufficient in-depth attention. This study aims to explore in depth how the construction of organizational culture—specifically values, rituals, narratives, and everyday practices—is understood, experienced, and made meaningful by educators, and how this meaning-making influences their motivation, engagement, and ultimately their performance. This research uses a qualitative phenomenological approach with a multi-site case study design in two senior high schools (one public and one private Islamic school) with distinct cultural characteristics. Data were collected through in-depth interviews with 15 educators and school principals, participatory observation over four months, and document analysis. Data were analyzed thematically using the interactive model by Miles, Huberman, and Saldaña (2014). The research findings reveal three main themes: (1)